Continuation of immunosuppression vs. immunosuppression weaning in potential repeat kidney transplant candidates: a care management perspective - Hickey, Michelle J.; Singh, Gurbir; Lum, Erik L. (Frontiers in Nephrology, 2023)
Management of immunosuppression in patients with a failing or failed kidney transplant requires a complete assessment of their clinical condition. One of the major considerations in determining immunosuppression is whether such an individual is considered a candidate for retransplantation. Withdrawal of immunosuppression in a retransplant candidate can result in allosensitization and markedly reduce the chances of a repeat transplant. In this review we summarize the effects of immunosuppression reduction on HLA sensitization, discuss the impacts of allosensitization in these patients, and explore reduction protocols and future directions. Risks of chronic immunosuppression, medical management of the failing allograft, and the effect of nephrectomy are covered elsewhere in this issue.